If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25(x + 39) = b Reorder the terms: 25(39 + x) = b (39 * 25 + x * 25) = b (975 + 25x) = b Solving 975 + 25x = b Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-975' to each side of the equation. 975 + -975 + 25x = -975 + b Combine like terms: 975 + -975 = 0 0 + 25x = -975 + b 25x = -975 + b Divide each side by '25'. x = -39 + 0.04b Simplifying x = -39 + 0.04b
| 3.5(3x-8)=x | | -(3-15y)=12 | | -(6x-3)=-9 | | 3-6x=2+6x | | 1/3(12x-36)+4=x+25 | | 5k-3/2=4 | | 2b+5=b+13 | | xy-4x=12 | | 6y-9(5y-8)= | | -3x-8+2x=8 | | 4.6+10m=8.81 | | 3(2x-2)+5=6(x+1) | | -9(v+2)+4v+7=8v+8 | | 76x-9=4x | | -3x+9x-41=97 | | 5x-2=1+3x | | X+21=3X-1 | | 22+6z+95=b | | 2(2x+3x)-10=30 | | 12x^3+6x^2+24x= | | 24/5x5/9 | | 2c+12=3c+c+6 | | -4y+4y=16 | | 2+x/3=-6 | | 3(x+1)=2.4x+22 | | 5a-(8-a)=4a+8 | | -4=7x-1*-8 | | x-9-3x=2x-7 | | 2x=11x+15 | | 5-2x/3=7 | | v^5+64v^3=0 | | 4s-17=25 |